2018
DOI: 10.1007/s00167-018-4958-7
|View full text |Cite
|
Sign up to set email alerts
|

Atopic dermatitis is a novel demographic risk factor for surgical site infection after anterior cruciate ligament reconstruction

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…High heterogeneity was found in the results. The sensitivity analysis showed that the study of Kawata et al 15 was the main source of the heterogeneity; removing this study reduced the I 2 to 38%, and the pooled analysis of the remaining studies still showed significant differences (OR 1.64, 95% CI 1.37 to 1.97, p<0.00001). The main source of heterogeneity in this study might be the short follow-up time, as patients were only observed during hospitalisation.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…High heterogeneity was found in the results. The sensitivity analysis showed that the study of Kawata et al 15 was the main source of the heterogeneity; removing this study reduced the I 2 to 38%, and the pooled analysis of the remaining studies still showed significant differences (OR 1.64, 95% CI 1.37 to 1.97, p<0.00001). The main source of heterogeneity in this study might be the short follow-up time, as patients were only observed during hospitalisation.…”
Section: Resultsmentioning
confidence: 89%
“…Following the review of the titles and abstracts, 41 studies were appropriate and were eligible for potential inclusion. After full text review, 23 studies9–16 24–38 were finally included (figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite there being many reports on the surgical procedure for knee ligament reconstruction, Original especially the anterior cruciate ligament determination of burr hole positions, selection of tendon grafts, and so on [1][2][3][4][5][6][7][8][9][10][11] , there have been few reports on infection prevention [12][13][14][15][16][17][18][19][20][21][22] and no reports on the sterilization of reconstruction materials using povidone-iodine during the surgical procedure. We have previously reported on the surgical procedure and outcomes of knee ligament reconstruction 23 .…”
Section: Introductionmentioning
confidence: 99%